Assessing the Path towards Sustainable Transport in Europe: An Integrated Model - Zachariadis, Theodoros (My University, 2005)
Sustainable development is a concept that for a long time had been accepted implicitly or explicitly as an important ingredient in formulating long-term strategies, although discussion often remained in the qualitative sphere. Apart from atmospheric pollution concerns in urban areas as well as climate change, the emergence of a great number of additional sustainability concerns in recent years (concerning bio-diversity, transport congestion, social exclusion, regional imbalances with their attendant political risks, etc.) has posed particular challenges to analysts with respect to integration and quantification of these problems. One of the major issues in this agenda is transport, which is worldwide accepted as a priority area in sustainability discussions (EEA, 2002; European Commission, 2001; IEA, 2002; WBCSD, 2001; World Bank, 1996). Work on sustainable transport is well in progress, both in the research field and in policy-oriented studies, concentrating primarily on emissions of air pollutants (causing health problems) and greenhouse gases (affecting climate change) and expanding to other sustainability concerns such as congestion, noise and accidents. Because of the inherent complexity of this sector in comparison to most other branches of economic activity due to the millions of travellers involved, policy measures often have to be taken at local scale and respecting local particularities. In such cases, instead of concrete quantified proposals, it is possible to provide policy guidelines only, pointing to successful pilot projects around the world (OECD, 2002).
Keywords: Emissions; Congestion; Noise; Accidents